2009
DOI: 10.4314/bjpm.v11i1.48820
|View full text |Cite
|
Sign up to set email alerts
|

Seroevidence Of Chlamydia Trachomatis Infection In Infertile Male And Its Association With Semen Quality In University Of Benin Teaching Hospital, Benin City, Nigeria

Abstract: Given the lack of information concerning the role of Chlamydia trachomatis in male infertility, it has become imperative to analyse the quality of semen of male with seroevidence of antibody to Chlamydia trachomatis infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
0
4
1
Order By: Relevance
“…C. trachomatis is known to be highly endemic in Nigeria with variation in distribution within various regions of the country (Okoror, 2010). The prevalence report of this study is close to 24 % among infertile males in Benin City (Ibadin et al, 2009), but quite less than 62.6% recorded by Okoror & Agbonlahor (2012), among infertile males in some parts of Nigeria. The prevalence in the current study is quite higher than 9.8% in Enugu, Nigeria (Ikeme et al, 2011).…”
contrasting
confidence: 39%
“…C. trachomatis is known to be highly endemic in Nigeria with variation in distribution within various regions of the country (Okoror, 2010). The prevalence report of this study is close to 24 % among infertile males in Benin City (Ibadin et al, 2009), but quite less than 62.6% recorded by Okoror & Agbonlahor (2012), among infertile males in some parts of Nigeria. The prevalence in the current study is quite higher than 9.8% in Enugu, Nigeria (Ikeme et al, 2011).…”
contrasting
confidence: 39%
“…In an earlier study, Suominen et al, (1993) reported elevated levels of Chlamydia trachomatis as against 35 % observed in 28 oligospermia patients (Bjerke and Pourvis, 1992). Ibadin et al, (2009) observed 24 % out of 156 infertile male patients.…”
Section: Resultsmentioning
confidence: 99%
“…A similar conclusion about a bacterial reservoir function for the male was reached by other authors (Toth et al, 1996) that noted the incidence of vaginits, salpingitis, herpes and urinary tract infection in 1350 infertile couples and was generally higher in women whose husbands had reported a previous history of genitor-urinary infection. Another possibility is that Chlamydia trachomatis may influence infertility by inducing sperm autoantibodies (Soffert et al, 1990;Ibadin et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors, however, concluded that C. trachomatis may be an independent risk factor affecting the quality of semen and male infertility. 35 Osegbe & Amaku 36 conducted a prospective study in Nigeria on the causes of male infertility using 504 patients. They concluded that the major causes were varicocele, infection, bilateral testicular failure, idiopathic oligospermia, multifactorial, cryptorchidism, sexual problems, and surgical injury.…”
mentioning
confidence: 99%